ANALYSIS ON EARLY CHILDHOOD SEXUAL ABUSE AND THE IMPLICATIONS IN ISLAMIC EDUCATION - Erhamwilda Erhamwilda; Nurul Afrianti (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
Fulfillment of children's rights has been a concern of Indonesia stated in the ratification of the Convention on the Rights of the Child and Act No. 23 of 2002 on Child Protection. However, violence against children is increasing each year. The most dominant violence emerged in recent years is sexual abuse committed against children aged 5 to 11 years, and the perpetrators of sexual abuse are close with the children. Concern about cases of sexual abuse in early childhood and their impact, should be followed by an effort to develop a variety of approaches and methods of sex education in accordance with religious and cultural values in which children live.